ULAR TANGGA KARIER SEBAGAI MEDIA LAYANAN BIMBINGAN KARIER UNTUK SISWA SEKOLAH DASAR - Putu Agus Indrawan; Suriata Suriata (Jurnal Bimbingan dan Konseling Borneo, 2021)
ABSTRACTThe purpose of this research is to create a simulation game Snakes and Ladders Career which is used by Guidance and Counseling teachers to develop insight and career readiness of elementary school students. The steps of this research development are (1) preparation, (2) preparation of the initial product, (3) expert test, (4) revision of the first product, 5) field test, and 6) revision of the final product. The product trial was conducted on 9 users and 2 experts. The resulting product specifications are in the form of a snake and ladder graphic media with a size of 3x3 m and dice size 20x20x20 cm as well as a guide book. The game media "career ladder snake" is declared to have very high validity based on the results of validation by media experts, material experts and users. So that the overall assessment of the validators stated that the "career ladder snake" game media was worthy of being used as a game medium for students in elementary school. Why is that the result? The game media that has been developed is feasible to use because the ratings from users and experts state that there is no need for significant improvements. This study can be used to produce game media that provide an understanding of the types of professions for elementary school students. Keywords : game media; career ladder snake, elementary school, career guidance AbstrakTujuan penelitian ini adalah menciptakan permainan simulasi Ular Tangga Karier yang digunakan oleh guru Bimbingan dan Konseling untuk mengembangkan wawasan dan kesiapan karier siswa Sekolah Dasar. Langkah-langkah penelitian pengembangan ini adalah (1) persiapan, (2) penyusunan produk awal, (3) uji ahli, (4) revisi produk pertama, 5) uji lapangan, dan 6) revisi produk akhir. Uji coba produk dilakukan pada 9 pengguna dan 2 ahli.  Spesifikasi produk yang dihasilkan berupa media grafis ular tangga dengan ukuran 3x3 m dan dadu ukuran 20x20x20 cm serta buku panduannya. Media permainan “ular tangga karier” dinyatakan memiliki validitas sangat tinggi berdasarkan hasil validasi oleh ahli media, ahli materi dan pengguna. Sehingga secara keseluruhan penilaian dari para validator menyatakan media permainan “ular tangga karier” layak digunakan sebagai media permainan kepada peserta didik di sekolah dasar. Kenapa hasilnya demikian? Media permainan yang dikembangkan telah layak digunakan karena penilaian dari pengguna dan ahli menyatakan tanpa perlu perbaikan yang signifikan. Studi ini dapat digunakan untuk menghasilkan media permainan yang memberikan pemahaman jenis-jenis profesi bagi siswa sekolah dasar.  Kata kunci: media permainan; ular tangga karier, sekolah dasar, bimbingan karier